PREOPERATIVE SCREENING FOR BLOOD-BORNE INFECTIONS – ESSENTIAL TOOL FOR PATIENTS AND HEALTHCARE - Muhammad Wasif Saleem; Abdul Samad Gichki; Mohammad Afzal Khaliq; Shazia Hashmat; Sadaf Fatima; Tayyab Uddin Khand (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
INTRODUCTION: The aim of this study was to examine the magnitude of viral infections as a global health problem, affecting millions around the world. Universal preoperative blood-born HIV virus, HBV, HCV testing has been identified as a universal precautionary risk mitigation strategy. As a universal measure, safety kits are for the surgical team and post-exposure prophylaxis as further protection is mandatory. For patients prior to the onset of AIDS/liver cirrhosis/ hepatocellular carcinoma, early diagnosis of the disease and its treatment is often helpful. The purpose of this analysis was the measurement of HIV/HCV/HBV seroprevalence for successful control programmes. PATIENTS AND METHODS: In collaboration with the Department of Pathology of the Indus Medical College Hospital, the research was carried out in the Department of Surgery and ALlied, Indus Medical College Tando Muhammad Khan. This analysis is a prospective study for the period from January 2019 to September 2019. Both patients admitted to elective/emergency surgery in the surgery department or those treated conservatively were included in the report. Visitors to The follow-up were removed. RESULTS: A total of 305 patients admitted to the surgery department have been screened for HBV, HCB and HIV. Hepatitis C (HCV) was a common infection, followed by HBV, but there were also co-infections. The common age group affected was 21-50 years, with a male: female 3.28:1 ratio. CONCLUSION: As part of routine pre-operative investigations, screening for HIV, HBV and HCV is mandatory in tertiary care centres in order to determine their prevalence and to prepare better preventive strategies.